Electromagnetic shielding thin film material with flexible multilayer structure and preparation method of electromagnetic shielding thin film material

PAN nanofiber films were prepared by electrospinning technology and loaded with MXene on its surface to form a multi-layer structure electromagnetic shielding film material, which solved the problems of conformity and mechanical properties of existing electromagnetic shielding materials and achieved high-performance electromagnetic shielding effect.

CN119820947APending Publication Date: 2025-04-15SOUTHEAST UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411981581.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials are difficult to conform, have high density and hardness, poor mechanical properties, and the preparation methods of high-performance electromagnetic shielding materials have the problem of too many conductive materials causing the decline in the mechanical properties of the material.

Method used

Electrospinning technology is used to prepare PAN nanofiber films, and MXene is loaded on the surface of the PAN fiber film by vacuum suction filtration and hot pressing to form an electromagnetic shielding film material with a flexible multi-layer structure.

Benefits of technology

A thin film material with low density, excellent flexibility and high electromagnetic shielding performance is achieved. The electromagnetic shielding performance is up to 82dB in the frequency band of 12GHz to 18GHz, and the mechanical properties and flexibility of the material can be taken into account.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820947A_ABST
    Figure CN119820947A_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic shielding thin film material with a flexible multilayer structure and a preparation method of the electromagnetic shielding thin film material. The electromagnetic shielding thin film material is a multilayer-structure thin film material composed of electrostatic spinning fibers and MXene loaded on the surfaces of the fibers. The preparation method of the high-performance electromagnetic shielding thin film material with the flexible light and thin multilayer structure comprises the following steps: preparing nanofiber made of a polyacrylonitrile (PAN) material by using an electrostatic spinning technology, obtaining MXene by using an etching method, and enabling the MXene to be attached to the surface of the fiber by using a vacuum suction filtration method. And finally, alternately superposing the fibers and MXene to combine the fibers and the MXene through a hot pressing method to prepare the high-performance electromagnetic shielding thin film material with a flexible, light and thin multilayer structure. The electromagnetic shielding effect of the material is enhanced by utilizing the structural advantage of a multi-layer structure. The electromagnetic shielding performance can reach 82dB, the density is 0.350 g / cm < 3 >, the flexible electromagnetic shielding material has excellent flexibility and electromagnetic shielding performance, and a new strategy is provided for solving the problem of electromagnetic wave pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flexible materials, and in particular to an electromagnetic shielding film material with a flexible multi-layer structure and a preparation method thereof. Background Art

[0002] With the development and progress of science and technology, wearable flexible communication devices are widely used, and their requirements for electromagnetic shielding are gradually increasing. Traditional electromagnetic shielding materials are often single metals or metal coatings. They have the characteristics of high density and high hardness, making them difficult to wear and conformal. At the same time, electrospinning technology can prepare flexible fiber films with excellent flexibility. Loading conductive materials on the surface of electrospun films is a method to obtain flexible electromagnetic shielding materials. However, to obtain high-performance electromagnetic shielding materials, it may be necessary to add a lot of conductive materials to reduce the square resistance of the material, which will damage the mechanical properties and flexibility of the material and affect the wearable comfort.

[0003] Prior art A flexible, highly conductive PVC-based electromagnetic shielding composite film and a preparation method thereof. The preparation method comprises the following steps: (1) dispersing PVC and carbon nanofillers in a solvent, stirring and degassing to obtain a casting liquid; (2) applying the casting liquid on a substrate; (3) naturally covering the applied casting liquid with a cloth, and then heating until the solvent evaporates and phase transformation occurs to form the film, and by means of gravity extrusion of the cloth during the film forming process, the thickness of the composite film is reduced, the connectivity of the carbon nanofiller network and the content of the carbon nanofiller per unit volume are increased, and a flexible, highly conductive PVC-based electromagnetic shielding composite film is obtained. However, since the electromagnetic shielding film is a mixture of conductive materials and polymers, the polymer will reduce the connection of the conductive path to a certain extent, thereby reducing the electromagnetic shielding performance of the film.

[0004] The prior art provides an electromagnetic shielding film and a preparation method thereof, wherein the preparation method comprises preparing MXene powder based on MAX phase material, lithium fluoride and hydrochloric acid; preparing ferrite@MXene composite material based on the MXene powder and ferrite raw material, wherein the ferrite raw material comprises at least one of nickel chloride hexahydrate and cobalt chloride hexahydrate; preparing electrospinning solution based on the ferrite@MXene composite material, polyacrylonitrile and DMF solution; electrospinning the electrospinning solution as raw material to obtain an electrospun membrane; and high-temperature carbonizing the electrospun membrane to obtain an electromagnetic shielding film. The electromagnetic shielding film of the present invention has multiple pores to improve the impedance mismatch phenomenon, so that more electromagnetic waves are reflected multiple times inside the pores and then absorbed. However, due to the decrease in mechanical properties of polyacrylonitrile after high-temperature carbonization, the flexible characteristics cannot be exerted to a certain extent. Summary of the invention

[0005] Purpose of the invention: To address the problems in the prior art of electromagnetic shielding materials, such as difficulty in conforming, high density, high hardness and poor mechanical properties, the present invention optimizes the material structure, provides a flexible, thin film material with high electromagnetic shielding performance, and also provides a method for preparing the above-mentioned composite material.

[0006] Technical solution: The present invention discloses a method for preparing a flexible multi-layer electromagnetic shielding film material, which is characterized by comprising the following steps:

[0007] Step 1: Preparation of PAN fiber film, dissolving PAN powder in NN-dimethylformamide to obtain PAN solution, and using a roller as an electrospinning receiving device to prepare PAN fiber film by electrospinning;

[0008] Step 2: Etching of MXene: lithium fluoride is added to a mixed solvent of hydrochloric acid and water, stirred, and then MAX is added, treated in an oil bath, washed to a pH of 6, ultrasonicated, and centrifuged to obtain MXene;

[0009] Step 3: Preparation of a flexible multilayer structured electromagnetic shielding film material. Place the PAN fiber film prepared in step 1 on a filter bottle with a frosted mouth, load the MXene prepared in step 2 on the surface of the PAN fiber film by vacuum filtration to obtain a film material, dry the obtained film material, stack the multiple layers of film material and then hot-press to prepare a flexible multilayer structured electromagnetic shielding film material.

[0010] The present invention also discloses a flexible multi-layer electromagnetic shielding film material prepared by the preparation method, characterized in that the film material consists of PAN nanofibers and MXene.

[0011] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: a flexible, thin, multi-layer structure of high-performance electromagnetic shielding film material with low density and excellent flexibility. The electromagnetic shielding performance of the multi-layer structure is as high as 82dB in the 12GHz to 18GHz frequency band.

[0012] The flexible, light, and multi-layered high-performance electromagnetic shielding film material prepared by the present invention has the advantages of light density and good flexibility compared to existing electromagnetic shielding materials; the PAN nanofiber film is prepared by electrospinning technology. The prepared nanofibers have a main diameter of 100-200nm, a large fiber aspect ratio, and a high porosity, which enable them to have very strong flexibility and mechanical properties. MAX is further etched to form MXene, and hydrochloric acid and lithium fluoride are used to etch MAX, which can etch away the aluminum element in MAX. After ultrasonic stripping, a single-layer structure of MXene is formed, which has high electrical conductivity and a rich functional group structure on its surface. The PAN nanofibers can be tightly combined with the functional groups on the surface of MXene through chemical bonds and intermolecular van der Waals forces to form a highly conductive flexible electromagnetic shielding film.

[0013] Through hot pressing technology, single-layer PAN and MXene films are hot pressed to form a multi-layer electromagnetic shielding film. In the electromagnetic shielding process, electromagnetic wave shielding mainly includes reflection and absorption. At the same time, reflection in the electromagnetic shielding process is mainly due to the impedance mismatch between the material and the air. The multi-layer electromagnetic shielding structure significantly increases the interface between the conductive layer and the non-conductive layer, and increases the impedance mismatch interface, thereby achieving multiple reflections of electromagnetic waves inside the material. Under the condition of the same conductive material, the multi-layer structure is conducive to improving the electromagnetic shielding performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A flow chart for preparing a flexible, thin, multi-layered high-performance electromagnetic shielding film material;

[0015] Figure 2 is the SEM image of PAN fiber;

[0016] Figure 3 This is a side SEM image of a flexible, thin, multi-layered high-performance electromagnetic shielding film material;

[0017] Figure 4 This is a flexible display picture of a multi-layer electromagnetic shielding film;

[0018] Figure 5 The figure is a comparison chart of the electromagnetic shielding performance of thin film materials with different multi-layer structures. DETAILED DESCRIPTION

[0019] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0020] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0021] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0022] An embodiment of the present application provides a method for preparing a flexible multi-layer electromagnetic shielding film material, comprising the following steps:

[0023] Step 1: Preparation of PAN (polyacrylonitrile) fiber film, dissolving PAN powder in NN-dimethylformamide to obtain PAN solution, and using a roller as an electrospinning receiving device to electrospin to prepare PAN fiber film;

[0024] Step 2: Etching of MXene: lithium fluoride is added to a mixed solvent of hydrochloric acid and water, stirred, MAX is added, oil bath treatment is performed, washing is performed to reach pH=6, ultrasonication is performed, and centrifugation is performed to obtain MXene;

[0025] Step 3: Preparation of a flexible multilayer electromagnetic shielding film material, placing the PAN fiber film prepared in step 1 on a filter bottle with a frosted mouth, loading the MXene prepared in step 2 on the surface of the PAN fiber film by vacuum filtration to obtain a film material, drying the obtained film material, superimposing and hot pressing the multilayer film material to obtain a flexible multilayer electromagnetic shielding film material. For detailed preparation process, see Figure 1 shown.

[0026] In one embodiment, in step 1, the mass fraction of PAN in the PAN solution is 8 wt %-15 wt %.

[0027] In one embodiment, in step 1, the drum is used as a receiving device for electrospinning, and the electrospinning process parameters are as follows:

[0028] The spinning speed is 0.5 mL / h to 1.5 mL / h, the voltage is 15 kV to 22 kV, the spinning distance is 11 cm to 14 cm, the rotation speed of the drum is 800 rpm to 1000 rpm, and the spinning time is 3 h to 6 h.

[0029] In one embodiment, in step 2, the ratio of hydrochloric acid to water is 3:1, the mass fraction of lithium fluoride is 4wt%-6wt%, and the mass fraction of the added MAX is 4wt%-6wt%.

[0030] In one embodiment, in step 2, the oil bath treatment has an oil bath temperature of 30°C-40°C, an oil bath time of 18h-36h, an ultrasonic time of 40min-60min, a centrifugal speed of 3000rpm-4000rpm, and a centrifugal time of 40min-60min.

[0031] In one embodiment, in step 3, the MXene loading concentration is 0.5 mg / cm 2 -4.0mg / cm 2 The drying conditions are vacuum, the drying temperature is 50℃-70℃, and the drying time is 4h-6h.

[0032] In one embodiment, in step 3, the number of film stacking layers is 1 to 4.

[0033] In one embodiment, in step 3, the hot pressing temperature is 150° C.-180° C., and the hot pressing time is 5 min-10 min.

[0034] An embodiment of the present application provides a flexible multi-layer electromagnetic shielding film material prepared by the preparation method, wherein the film material is composed of PAN nanofibers and MXene.

[0035] In one embodiment, the PAN nanofibers and MXene are alternately stacked to form a multilayer structure film material.

[0036] In one embodiment, the MXene includes Ti3C2.

[0037] Example 1

[0038] a. Use vacuum assisted filtration and hot pressing process to prepare flexible, thin, multi-layered high-performance electromagnetic shielding film materials:

[0039] (1) Preparation of PAN fiber film: PAN powder was dissolved in NN-dimethylformamide to obtain a solution with a PAN mass fraction of 10 wt%. The spinning speed was set to 0.5 mL / h, the voltage was 20 kV, the spinning distance was 14 cm, the rotation speed of the roller was 800 rpm, and the spinning time was 5 h. A flexible PAN film was obtained, and its SEM was as follows: Figure 2 shown.

[0040] (2) Etching of MXene: Add 5 wt% LiF to a mixed solvent of hydrochloric acid and water in a volume ratio of 3:1 and stir for 30 min. Gradually add 5 wt% Ti3AlC2 to the above solution and continue stirring in a 35°C oil bath for 24 h to peel off Al. The resulting suspension is rinsed with deionized water several times until the pH is 6, and ultrasonicated for 60 min. The solution after ultrasonication is centrifuged at 3500 rpm for 1 h, and the layered Ti3C2Tx Dark green supernatant of nanosheets (i.e., monolayer dispersed MXene solution).

[0041] (3) Preparation of flexible, thin, multi-layered high-performance electromagnetic shielding film materials: PAN fiber film was placed in a filter bottle with a frosted mouth, and a 1 mg / cm2 load was applied to the PAN surface by vacuum filtration. 2 The obtained thin film material was dried at 60℃ for 5h, and four layers of thin film material were stacked together and hot pressed at 150℃ for 5min. The side SEM image is as follows Figure 3 As shown in the actual picture. Figure 4 shown.

[0042] b. Electromagnetic shielding performance test

[0043] Based on the waveguide method, the S parameters of the film are tested using a vector network analyzer in the frequency range of 12 GHz to 18 GHz. The known S parameters can be calculated:

[0044] R=|S 11 | 2 =|S 22 | 2 (1)

[0045] T=|S 12 | 2 =|S 21 | 2 (2)

[0046] A+R+T=1 (3)

[0047] SE T =-10lgT (4)

[0048] SE R =-10lg(1-R) ​​(5)

[0049]

[0050] Where S 11 , S 22 is the reflection coefficient of port 1 and port 2. 12 and S 21 are the forward and reverse transmission coefficients respectively. A, R, and T are the absorption coefficient, reflection coefficient, and transmission coefficient respectively. T (Unit: dB), SE R , SE A , SE M They are total, reflection, absorption, and multiple internal scattering electromagnetic shielding effectiveness. A When it is greater than 15dB, SE M Can be ignored.

[0051] Table 1 shows the electromagnetic shielding effectiveness of the four-layer film material of Example 1

[0052]

[0053] The results are shown in Table 1. The electromagnetic shielding effectiveness of the flexible multilayer structure electromagnetic shielding film can reach 82dB in the frequency range of 12GHz to 18GHz. The structure of alternating conductive layers and insulating layers increases the interface with impedance mismatch and enhances the number of electromagnetic wave reflections. As a result, the film obtains excellent electromagnetic shielding performance. The specific electron microscope image of the material is shown in Figure 2 shown.

[0054] Example 2

[0055] a. Use vacuum-assisted filtration to prepare flexible, thin, multi-layered high-performance electromagnetic shielding film materials:

[0056] (1) Preparation of PAN fiber film: PAN powder was dissolved in NN-dimethylformamide to obtain a solution with a PAN mass fraction of 10 wt%. The spinning speed was set to 1 mL / h, the voltage was 18 kV, the spinning distance was 13 cm, the rotation speed of the drum was 900 rpm, and the spinning time was 5 h.

[0057] (2) Etching of MXene: 4 wt% LiF was added to a mixed solvent of hydrochloric acid and water in a volume ratio of 3:1 and stirred for 30 min. 4 wt% Ti3AlC2 was gradually added to the above solution and stirred in a 30°C oil bath for 36 h to remove Al. The obtained suspension was rinsed with deionized water several times until the pH was 6, and ultrasonicated for 60 min. The solution after ultrasonication was centrifuged at 4000 rpm for 1 h, and the layered Ti3C2T x Dark green supernatant of nanosheets (i.e., monolayer dispersed MXene solution).

[0058] (3) Preparation of flexible, thin, multi-layered high-performance electromagnetic shielding film materials: PAN fiber film was placed in a filter bottle with a frosted mouth, and a 4 mg / cm3 load was applied to the PAN surface by vacuum filtration. 2 The obtained thin film material was dried at 60°C for 6h, and the single-layer thin film materials were stacked together and hot-pressed at 150°C for 5min.

[0059] b. Electromagnetic shielding performance test

[0060] Based on the waveguide method, the S parameters of the film are tested using a vector network analyzer in the frequency range of 12GHz to 18GHz. The known S parameters can be calculated:

[0061] R=|S 11 |2 =|S 22 | 2 (1)

[0062] T=|S 12 | 2 =|S 21 | 2 (2)

[0063] A+R+T=1 (3)

[0064] SE T =-10lgT (4)

[0065] SE R =-10lg(1-R) ​​(5)

[0066]

[0067] Where S 11 , S 22 is the reflection coefficient of port 1 and port 2. 12 and S 21 are the forward and reverse transmission coefficients respectively. A, R, and T are the absorption coefficient, reflection coefficient, and transmission coefficient respectively. T (Unit: dB), SE R , SE A , SE M They are total, reflection, absorption, and multiple internal scattering electromagnetic shielding effectiveness. A When it is greater than 15dB, SE M Can be ignored.

[0068] Table 2 shows the electromagnetic shielding effectiveness of the single-layer film material of Example 2

[0069]

[0070] The results are shown in Table 2. The film having the same conductive material but without a multilayer structure has an electromagnetic shielding effectiveness SE of only 53 dB in the frequency range of 12 GHz to 18 GHz.

[0071] Example 3

[0072] Changing the number of layers in a multi-layer structure

[0073] a. Use impregnation and carbonization process to prepare flexible, thin and high electromagnetic shielding performance carbon cloth composite materials:

[0074] (1) Preparation of PAN fiber film: PAN powder was dissolved in NN-dimethylformamide to obtain a solution with a PAN mass fraction of 10 wt%. The spinning speed was set to 0.5 mL / h, the voltage was set to 20 kV, the spinning distance was set to 14 cm, the rotation speed of the drum was set to 800 rpm, and the spinning time was set to 5 h.

[0075] (2) Etching of MXene: Add 5 wt% LiF to a mixed solvent of hydrochloric acid and water in a volume ratio of 3:1 and stir for 30 min. Gradually add 5 wt% Ti3AlC2 to the above solution and continue stirring in a 35°C oil bath for 24 h to peel off Al. The resulting suspension is rinsed with deionized water several times until the pH is 6, and ultrasonicated for 60 min. The solution after ultrasonication is centrifuged at 3500 rpm for 1 h, and the layered Ti3C2T x Dark green supernatant of nanosheets (i.e., monolayer dispersed MXene solution).

[0076] (3) Preparation of flexible, thin, multi-layered high-performance electromagnetic shielding film materials: PAN fiber film was placed in a filter bottle with a frosted mouth, and 2 mg / cm was loaded on the PAN surface by vacuum filtration. 2 The obtained thin film material was dried at 60°C for 5h, and the two layers of thin film materials were stacked together and hot pressed at 150°C for 5min.

[0077] b. Electromagnetic shielding performance test

[0078] Based on the waveguide method, the S parameters of the film are tested using a vector network analyzer in the frequency range of 12GHz to 18GHz. The known S parameters can be calculated:

[0079] R=|S 11 | 2 =|S 22 | 2 (1)

[0080] T=|S 12 | 2 =|S 21 | 2 (2)

[0081] A+R+T=1 (3)

[0082] SE T =-10lgT (4)

[0083] SE R =-10lg(1-R) ​​(5)

[0084]

[0085] Where S11 , S 22 is the reflection coefficient of port 1 and port 2. 12 and S 21 are the forward and reverse transmission coefficients respectively. A, R, and T are the absorption coefficient, reflection coefficient, and transmission coefficient respectively. T (Unit: dB), SE R , SE A , SE M They are total, reflection, absorption, and multiple internal scattering electromagnetic shielding effectiveness. A When it is greater than 15dB, SE M Can be ignored.

[0086] The results are shown in Table 3. The electromagnetic shielding effectiveness SE of the film material can reach 69dB in the frequency range of 12GHz to 18GHz.

[0087] Table 3 shows the electromagnetic shielding effectiveness of the double-layer film material of Example 3

[0088]

[0089] The reason why the product performance of Examples 1 and 2 is different is that the material structure is different. The multi-layer structure will significantly increase the number of impedance mismatches. The number of times the electromagnetic wave is reflected when passing through the material is different, which ultimately leads to different electromagnetic shielding performance. The reason why the product performance of Examples 1 and 3 is different is that the number of layers in the multi-layer structure is different, resulting in different numbers of impedance mismatches. The number of times the electromagnetic wave is reflected after passing through the material is different. Increasing the number of layers is conducive to increasing the number of impedance mismatches, resulting in different electromagnetic shielding performance.

[0090] Example 4

[0091] a. Use vacuum assisted filtration and hot pressing process to prepare flexible, thin, multi-layered high-performance electromagnetic shielding film materials:

[0092] (1) Preparation of PAN fiber film: PAN powder was dissolved in NN-dimethylformamide to obtain a solution with a PAN mass fraction of 8 wt%. The spinning speed was set to 0.5 mL / h, the voltage was 15 kV, the spinning distance was 14 cm, the rotation speed of the roller was 800 rpm, and the spinning time was 6 h. A flexible PAN film was obtained, and its SEM was as follows: Figure 2 shown.

[0093] (2) Etching of MXene: Add 5 wt% LiF to a mixed solvent of hydrochloric acid and water in a volume ratio of 3:1 and stir for 30 min. Gradually add 5 wt% Ti3AlC2 to the above solution and continue stirring in a 35°C oil bath for 24 h to peel off Al. The resulting suspension is rinsed with deionized water several times until the pH is 6, and ultrasonicated for 60 min. The solution after ultrasonication is centrifuged at 3000 rpm for 1 h, and the layered Ti3C2T x Dark green supernatant of nanosheets (i.e., monolayer dispersed MXene solution).

[0094] (3) Preparation of flexible, thin, multi-layered high-performance electromagnetic shielding film materials: PAN fiber film was placed in a filter bottle with a frosted mouth, and 1 mg / cm was loaded on the PAN surface by vacuum filtration. 2 The obtained thin film material was dried at 50°C for 4h, and the four layers of thin film material were stacked together and hot pressed at 150°C for 5min.

[0095] b. Electromagnetic performance shielding performance

[0096] The performance testing method is the same as that of Example 1, and its electromagnetic shielding performance is the same as that of Example 1.

[0097] Example 5

[0098] a. Use vacuum-assisted filtration to prepare flexible, thin, multi-layered high-performance electromagnetic shielding film materials:

[0099] (1) Preparation of PAN fiber film: PAN powder was dissolved in NN-dimethylformamide to obtain a solution with a PAN mass fraction of 10 wt%. The spinning speed was set to 1 mL / h, the voltage was 18 kV, the spinning distance was 13 cm, the rotation speed of the drum was 900 rpm, and the spinning time was 5 h.

[0100] (2) Etching of MXene: 4 wt% LiF was added to a mixed solvent of hydrochloric acid and water in a volume ratio of 3:1 and stirred for 30 min. 4 wt% Ti3AlC2 was gradually added to the above solution and stirred in a 30°C oil bath for 36 h to remove Al. The obtained suspension was rinsed with deionized water several times until the pH was 6, and ultrasonicated for 60 min. The solution after ultrasonication was centrifuged at 4000 rpm for 1 h, and the layered Ti3C2T x Dark green supernatant of nanosheets (i.e., monolayer dispersed MXene solution).

[0101] (3) Preparation of flexible, thin, multi-layered high-performance electromagnetic shielding film materials: PAN fiber film was placed in a filter bottle with a frosted mouth, and a 4 mg / cm2 load was applied to the PAN surface by vacuum filtration. 2The obtained thin film material was dried at 60°C for 6h, and the single-layer thin film materials were stacked together and hot-pressed at 150°C for 5min.

[0102] b. Electromagnetic performance shielding performance

[0103] The performance testing method is the same as that of Example 2, and its electromagnetic shielding performance is the same as that of Example 2.

[0104] Example 6

[0105] a. Use impregnation and carbonization process to prepare flexible, thin and high electromagnetic shielding performance carbon cloth composite materials:

[0106] (1) Preparation of PAN fiber film: PAN powder was dissolved in NN-dimethylformamide to obtain a solution with a PAN mass fraction of 15 wt%. The spinning speed was set to 1.5 mL / h, the voltage was set to 22 kV, the spinning distance was set to 11 cm, the rotation speed of the drum was set to 1000 rpm, and the spinning time was set to 3 h.

[0107] (2) Etching of MXene: Add 6 wt% LiF to a mixed solvent of hydrochloric acid and water in a volume ratio of 3:1 and stir for 30 min. Gradually add 6 wt% Ti3AlC2 to the above solution and continue stirring in a 40°C oil bath for 18 h to peel off Al. The resulting suspension is rinsed with deionized water several times until the pH is 6, and ultrasonicated for 60 min. The solution after ultrasonication is centrifuged at 3500 rpm for 1 h, and the layered Ti3C2T x Dark green supernatant of nanosheets (i.e., monolayer dispersed MXene solution).

[0108] (3) Preparation of flexible, thin, multi-layered high-performance electromagnetic shielding film materials: PAN fiber film was placed in a filter bottle with a frosted mouth, and 0.5 mg / cm was loaded on the PAN surface by vacuum filtration. 2 The obtained thin film material was dried at 70°C for 4h, and the two layers of thin film materials were stacked together and hot pressed at 150°C for 5min.

[0109] b. Electromagnetic performance shielding performance

[0110] The performance testing method is the same as that of Example 3, and its electromagnetic shielding performance is the same as that of Example 3.

[0111] In general, the entire experimental process ensures that the total amount of conductive material is the same, and the same total amount of conductive material is divided into different structures to form different multilayer structures. The final multilayer structure enhances the reflection performance of the material; the high-performance electromagnetic shielding film material of the flexible, thin and multilayer structure of the present invention has light density and good flexibility, and the electromagnetic shielding performance is as high as 82dB in the 12GHz to 18GHz frequency band.

[0112] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a flexible multi-layer electromagnetic shielding film material, characterized in that: The following steps are involved: Step 1: Preparation of PAN fiber film, dissolving PAN powder in NN-dimethylformamide to obtain PAN solution, and using a roller as an electrospinning receiving device to electrospin to prepare PAN fiber film; Step 2: Etching of MXene: lithium fluoride is added to a mixed solvent of hydrochloric acid and water, stirred, MAX is added, oil bath treatment is performed, washing is performed to reach pH=6, ultrasonication is performed, and centrifugation is performed to obtain MXene; Step 3: Preparation of a flexible multilayer structured electromagnetic shielding film material. Place the PAN fiber film prepared in step 1 on a filter bottle with a frosted mouth, load the MXene prepared in step 2 on the surface of the PAN fiber film by vacuum filtration to obtain a film material, dry the obtained film material, stack the multiple layers of film material and then hot-press to prepare a flexible multilayer structured electromagnetic shielding film material.

2. The method for preparing the flexible multi-layer electromagnetic shielding film material according to claim 1, characterized in that: In step 1, the mass fraction of PAN in the PAN solution is 8wt%-15wt%.

3. The method for preparing the electromagnetic shielding film material with a flexible multilayer structure according to claim 1, characterized in that: In step 1, the drum is used as a receiving device for electrospinning, and the electrospinning process parameters are as follows: The spinning speed is 0.5 mL / h to 1.5 mL / h, the voltage is 15 kV to 22 kV, the spinning distance is 11 cm to 14 cm, the rotation speed of the drum is 800 rpm to 1000 rpm, and the spinning time is 3 h to 6 h.

4. The method for preparing the flexible multi-layer electromagnetic shielding film material according to claim 1, characterized in that: In step 2, the ratio of hydrochloric acid to water is 3:1, the mass fraction of lithium fluoride is 4wt%-6wt%, and the mass fraction of the added MAX is 4wt%-6wt%.

5. The method for preparing the flexible multi-layer electromagnetic shielding film material according to claim 1, characterized in that: In step 2, the oil bath treatment has an oil bath temperature of 30°C-40°C, an oil bath time of 18h-36h, an ultrasonic time of 40min-60min, a centrifugal speed of 3000rpm-4000rpm, and a centrifugal time of 40min-60min.

6. The method for preparing the electromagnetic shielding film material with a flexible multi-layer structure according to claim 1, characterized in that: In step 3, the MXene loading concentration is 0.5 mg / cm 2 -4.0mg / cm 2 The drying conditions are vacuum, the drying temperature is 50℃-70℃, and the drying time is 4h-6h.

7. The method for preparing the flexible multi-layer electromagnetic shielding film material according to claim 1, characterized in that: In step 3, the number of film stacking layers is 1 to 4.

8. The method for preparing the flexible multi-layer electromagnetic shielding film material according to claim 1, characterized in that: In step 3, the hot pressing temperature is 150° C.-180° C., and the hot pressing time is 5 min-10 min.

9. A flexible multi-layered electromagnetic shielding film material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The film material consists of PAN nanofibers and MXene.

10. The electromagnetic shielding film material with a flexible multilayer structure according to claim 9, characterized in that: The PAN nanofibers and MXene are alternately stacked to form a multilayer structure film material.

Citation Information

Patent Citations

  • Flexible nanofiber membrane with electromagnetic shielding and piezoresistive sensing performance and preparation method thereof

    CN114150496A

  • Lightweight porous MXene polyimide composite film as well as preparation method and application thereof

    CN117565496A

  • Ultrathin integrated flexible supercapacitor and preparation method and application thereof

    CN118231152A

  • Control system for distributing hot water

    KR1020240105336A